Panorama nacional dos estudantes público-alvo da educação especial na educação superior - Rocha, Luiz Renato Martins da (2019)
The target group of learners with special educational needs (SEN) in Higher Education totaled 37,927 of the 8,027,297 enrollments in 2015, corresponding to 0.47% (INEP, 2015b). It should be noted that, despite the small percentage, this public has been growing significantly in Higher Education in recent years, which indicates the constant need to create even more effective policies to guarantee access: admission, stay and institutions of higher education (HEI). In this sense, the data collected in the present research provide indications of how the Special Education in Higher Education in Brazil offers an opportunity for revision and orientation regarding the recognition and registration of SEN students in the Higher Education Census. Thus, we aimed to analyze and map SEN students in Higher Education in Brazil, taking as a data source the year 2015 and, more specifically, presenting a panorama of Higher Education based on the microdata of the Higher Education Census. In order to reach the proposed objective, we carried out a quantitative research with a descriptive and exploratory method. Data were processed using the SAS® program (Version 9.2) and software R (Version 3.3.1), which enabled access to the microdata through tables. Through Microsoft Office Excel®, the graphs and other tables were assembled, as well as the verification of the values found. As we understand that behind each of these numbers there is a life story, we perform its interpretation in the light of their interaction with the historical and social context. We also identify the imprecision of various data, usually due to misunderstandings in the collection of information (which may be caused by self-declaration or by those who feed such data in the INEP system), or by the impossibility of correcting data once informed and published, which generates distortions of information in relation to reality. In addition, despite the limitations of the data, it is clear that the SEN students are disadvantaged in relation to other people, since the conclusion of the course is still a challenge to be overcome, and access has been restricted to a small portion. For a better overview of Brazilian Higher Education, it is necessary to construct a data collection instrument at the national level, so that, at the time of the student's enrollment in the IES, all the information related to their condition is duly considered and the data presented in the Census indeed express a reliable picture for the construction of public policies.